PENGARUH INOVASI LAYANAN TERHADAP LOYALITAS KONSUMEN DENGAN KONSUMEN INOVATIF SEBAGAI VARIABEL MODERASI - Desi roziana; Novita Sari (Konsentrasi Manajemen Pemasaran Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2018)
The purpose of this study is to analyze the effect of service innovation on consumer loyalty and reveal consumer’s innovativeness role as moderator variable on consumer’s loyalty. This research uses quantitative approach. Size sample consist of 120 customers who lives in Kotabaru district. Data analysis used simple and multiple linear regression method. Based on the analysis, it is known that: 1) service innovation influenced consumer loyalty by 22.9% and the rest 77.1% influenced by other factors; 2) innovative consumers as moderating variables are able to influence the relationship between service innovation to loyalty of 44.6% and the remaining 55.4% influenced by other factors. Hence, based on customer innovativeness, retailer should build effective communication to every innovation to customer.